An awareness campaign decreases distracted driving among hospital employees at a rural trauma center. (21st March 2018) - Rana, Navpreet; Ross, Melissa; LaRock, Lisa; Mele, Jennifer; Cumbo, Nicole; Colom, Lauren; Trecartin, Andrew; Granet, Jason; Behm, Rob
Abstract: Objective: To evaluate whether an educational campaign on distracted driving will have an impact in a given community. Methods: Investigators were stationed in an employee parking lot of a 256-bed hospital to determine baseline distracted driving followed by a 4-week hospital-wide distracted-driving awareness campaign. The campaign included signs/posters in the hospital, a booth outside of the cafeteria with flyers, a large banner in the employee lot and an opportunity for people to sign a pledge form to drive distraction free. The same employee lot was observed at the same time of the day to re-assess distracted driving immediately following the campaign. The observations were repeated again one year later to evaluate the short and long-term impact of the campaign. Results: A total of 485 vehicles were observed pre-campaign, identifying 170 (35%) distracted drivers at baseline. The awareness campaign resulted in 525 people pledging to drive distraction free. Following the campaign, 495 vehicles were observed and the number of distracted drivers was 64 (12.9%), showing a significant decrease in the number of distracted drivers by 22.1% ( p  < 0.01). One year later, 530 drivers were observed with 150 (28%) displaying one form of distraction. Conclusions: A local distracted driving educational campaign resulted in a significant decrease in the number of distracted drivers immediately following the campaign. However, one year after the campaign, there was an increase in distracted driving. The proportion of distracted drivers was still significantly lower than the initial rate of distracted-drivers.